2018
DOI: 10.1016/j.aller.2017.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhaled medication on dental caries index in asthmatic children

Abstract: Suffering from asthma does not affect the risk of decay in primary teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…No significant differences were observed between both groups. 13 However, Arafa et al, found that the DMFT index in healthy children was 5.47 ± 2.16 and, in asthma children, 6.84 ± 1.81 (p = 0.04); 5 whereas Samec et al, observed that it was 1.69 ± 2.63 in healthy children and 7.01 ± 5.59 in asthma patients (p = 0.01). 11 Such differences may be because dental caries is a multifactorial infectious disease that depends on environmental, sociodemographic, behavioral, microbiological, and nutritional factors.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…No significant differences were observed between both groups. 13 However, Arafa et al, found that the DMFT index in healthy children was 5.47 ± 2.16 and, in asthma children, 6.84 ± 1.81 (p = 0.04); 5 whereas Samec et al, observed that it was 1.69 ± 2.63 in healthy children and 7.01 ± 5.59 in asthma patients (p = 0.01). 11 Such differences may be because dental caries is a multifactorial infectious disease that depends on environmental, sociodemographic, behavioral, microbiological, and nutritional factors.…”
Section: Discussionmentioning
confidence: 96%
“…5,11 Conversely, some studies have mentioned that there is no direct causal relationship between inhaler use and a higher prevalence of dental caries in asthma patients, compared to healthy subjects. 12,13 Understanding the impact of bronchial asthma on oral health would help to provide comprehensive dental care and establish public health strategies aimed at prevention.…”
Section: Original Articlementioning
confidence: 99%
“…No encontraron diferencia significativa entre ambos grupos. 13 Sin embargo, Arafa y cols., encontraron que el índice de CPOD en los pacientes pediátricos sanos fue de 5,47 ± 2,16 y, en los asmáticos, de 6,84 ± 1,81 (p = 0,04); 5 mientras que Samec y cols., encontraron que, en los pacientes pediátricos sanos, fue de 1,69 ± 2,63 y, en los asmáticos, de 7,01 ± 5,59 (p = 0,01). 11 Estas diferencias podrían deberse a que la caries dental es una enfermedad infectocontagiosa multifactorial que depende de una variedad de factores ambientales, sociodemográficos, conductuales, microbiológicos y nutricionales.…”
Section: Resultsunclassified
“…5,11 En contraparte, algunos estudios mencionan que no existe una relación directa causal entre el uso de inhaladores y una mayor prevalencia de caries dental en los pacientes asmáticos, en comparación con los pacientes sanos. 12,13 Comprender el impacto del asma bronquial en la salud bucal ayudaría a proporcionar una atención odontológica integral y a establecer estrategias de salud pública para una conducta preventiva.…”
Section: Adrenérgicos Anticolinérgicos Y O T R O S D E a C C I ó N Sunclassified
“…There is no consensus among researchers about association of asthma and its characteristics, medications with salivary changes, and dental caries among adolescents. There is no association between asthma and dental caries in deciduous dentition among children aged from 5 to 11 years 11,12,15,16 . However, studies among adolescents aged from 13 to 19 years have found association in permanent dentition, highlighting the cumulative impact of asthma over a period of time 9,10 .…”
Section: Introductionmentioning
confidence: 99%